Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Bank Syariah Indonesia di Jakarta Studi Kasus Bank Syariah Indonesia KC MH Thamrin: The Influence of Work Discipline and Work Motivation on Employee Performance at Bank Syariah Indonesia in Jakarta: A Case Study of Bank Syariah Indonesia KC MH Thamrin - Anas Hamdani; Mohammad Amas Lahat; Dani Chandra Utama (CV Warnak Johanna Nusantara, 2025)
This study aims to explain the partial and simultaneous influence between the variables of work discipline and work motivation on employee performance at Bank Syariah Indonesia KC Mh Thamrin. This type of research is quantitative research because it is related to numbers and statistics to test variables and hypotheses. Data processing uses the SPSS version 26 program, The population in this study amounted to 33 employees who are employees of Bank Syariah Indonesia KC Mh Thamrin. The researcher conducted several tests including multiple linear regression analysis, classical assumption tests, hypothesis tests and determination coefficient tests. With the sampling technique used, namely saturated samples. The results of the T-test show that work discipline and work motivation have a significant effect on employee performance with a significant value of 0.001 and 0.004 Ftable 3.32